Increased rupture of cypress pollen type due to atmospheric water in central and southeastern Spain - F. Aznar; L. Negral; S. Moreno-Grau; I. Costa; B. Lara; J. Romero-Morte; J. Rojo; R.M. Rodríguez-Arias; F. Fernández-González; R. Pérez-Badia; J.M. Moreno (Science of The Total Environment, 2024)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Raman-IR spectroscopic, and XRD analysis of selected samples from Fogo Island, Cabo Verde: Implications for ancient Martian volcanology - M. Aznar; A. Sanz-Arranz; S. Shkolyar; E.R. Sawyers; M. Konstantinidis; G. Lopez-Reyes; M. Veneranda; E.A. Lymer; J.R. Freemantle; M.G. Daly; E.A. Cloutis; F. Rull-Perez; et al. (Advances in Space Research, 2023)

Epibiotic Fauna on Cetaceans Worldwide: A Systematic Review of Records and Indicator Potential - S. Ten; J. A. Raga; F. J. Aznar (Frontiers in Marine Science, 2022)
Each individual cetacean is an ecosystem itself, potentially harboring a great variety of animals that travel with it. Despite being often despised or overlooked, many of these epizoites have been proven to be suitable bio-indicators of their cetacean hosts, informing on health status, social interactions, migration patterns, population structure or phylogeography. Moreover, epizoites are advantageous over internal parasites in that many of them can be detected by direct observation (e.g., boat surveys), thus no capture or dissection of cetaceans are necessary. Previous reviews of epizoites of cetaceans have focused on specific geographical areas, cetacean species or epibiotic taxa, but fall short to include the increasing number of records and scientific findings about these animals. Here we present an updated review of all records of associations between cetaceans and their epibiotic fauna (i.e., commensals, ecto- or mesoparasites, and mutualists). We gathered nearly 500 publications and found a total of 58 facultative or obligate epibiotic taxa from 11 orders of arthropods, vertebrates, cnidarians, and a nematode that are associated to the external surface of 66 cetacean species around the globe. We also provide information on the use as an indicator species in the literature, if any, and about other relevant traits, such as geographic range, host specificity, genetic data, and life-cycle. We encourage researchers, not only to provide quantitative data (i.e., prevalence, abundance) on the epizoites they find on cetaceans, but also to inform on their absence. The inferences drawn from epizoites can greatly benefit conservation plans of both cetaceans and their epizoites.

Deadly impalement of a blue shark Prionace glauca by a swordfish Xiphias gladius - J. PENADÉS-SUAY; J. TOMÁS; F. J. AZNAR (Mediterranean Marine Science, 2017)
In September, 2016, an adult female blue shark (Prionace glauca) 247 cm long stranded alive on the coast of Valencia (Spain, Western Mediterranean) but died shortly afterwards. The necropsy revealed ongoing pregnancy, with 65 embryos in early stage of development, and a healthy condition with no signs of starvation. Two fishing hooks surrounded by scarred tissue were detected in the mandible, indicating past interaction with fisheries. In addition, a fragment of the tip of a swordfish (Xiphias gladius) rostrum (length: 18 cm long, width: 0.5 cm (distal) and 3 cm (proximal)) was removed from the animal. The fragment had pierced the head producing an incision of 3.5 cm close to the left eye, crossing the head anterior to the pre-orbital process. No apparent damage was observed in the olfactory capsule or the eye, but the fragment had penetrated both sides of the skull causing extensive lesions in the brain, which were inferred to be the cause of death. Allometric analysis suggested that the swordfish was ca. 110 cm long, corresponding to a juvenile 1-2 yrs old. Swordfish had previously been reported driving their rostrum into pelagic sharks, allegedly as a defensive strategy. However, this is the first report of impalement as the direct cause of death in blue sharks.

Geological risk assessment of Amtoudi Agadir in southern Morocco: a key case for sustainable cultural heritage - P. Robles-Marín; F. Guerrera; M. Martín-Martín; G. Raffaelli; F. J. Alcalá; J. Tejera de León; T. E. Cherkaoui; L. Asebriy; I. E. El Amrani; S. Moliner-Aznar (Natural Hazards, 2015)

Evaluation of phenotypic and PCR-based approaches for routine analysis of Bacillus cereus group foodborne isolates - J. F. Martínez-Blanch; G. Sánchez; E. Garay; R. Aznar (Antonie van Leeuwenhoek, 2011)

Monitoring In Vivo Load Transmission Through an External Fixator - J. Grasa; M. J. Gómez-Benito; L. A. González-Torres; D. Asiaín; F. Quero; J. M. García-Aznar (Annals of Biomedical Engineering, 2010)

Diet of Balaenophilus spp. (Copepoda: Harpacticoida): feeding on keratin at sea? - F. J. Badillo; L. Puig; F. E. Montero; J. A. Raga; F. J. Aznar (Marine Biology, 2007)

Fluorescence-Labeled Pyrenesulfonamide Response for Characterizing Polymeric Interfaces in Composite Materials - J. González-Benito; A. J. Aznar; J. Lima; F. Bahia; A. L. Maçanita; J. Baselga (Journal of Fluorescence, 2000)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)